НАУКОВА КОНЦЕПЦІЯ РОЗРОБКИ ВИСОКОВОЛЬТНИХ ЕЛЕКТРОТЕХНІЧНИХ СИСТЕМ РЕЗОНАНСНОГО ТИПУ З ШВИДКОДІЮЧИМИ КЕРУВАННЯМ І ПАРАМЕТРИЧНОЮ СТАБІЛІЗАЦІЄЮ РЕЖИМІВ НАВАНТАЖЕННЯ - Щерба, А.А.; Вінниченко, Д.В.; Супруновська, Н.І. (Інститут електродинаміки НАН України, Київ, 2024)
A new scientific concept has been developed for the creation of high-voltage electro-technical systems (ETS) of a resonant type based on the implementation in them of series high-quality inductive-capacitive circuits (ICC) and high-frequency (HF) resonant currents. This makes it possible to repeatedly increase the alternating voltage on the reactive elements of the ICC and on the load connected in parallel to one of the elements, and to ensure a significant decrease in the impulse energy of the ETS without changing their average power, as well as to increase the speed of control and parametric stabilization of the load modes of the ETS even with a rapid decrease in the electrical resistance of this load to almost zero, as in the case of electrical breakdown of its insulation. The generation of resonant currents with a frequency of up to 40 kHz in the ICC, which has a coil with an inductance of ~ 25 mH and a Q factor up to 270 (made of multi-core twisted copper wires of the " litzendraht " type) and a ceramic capacitor with a capacity of ~ 3.5 nF and a Q factor > 1000, ensures the realization of the QICC up to 260 and the corresponding increase in the ratio of the ETS output voltage to the input voltage without the use of step-up transformers. When connecting such an ETS to a source of alternating voltage of 220 V, a voltage of up to 40 kV can be generated at the output of the ETS. A significant increase in the frequency of currents leads to a significant decrease in the mass-dimensional characteristics of ETS and the possibility of creating their samples mobile (weighing up to 5 kg), and if necessary, autonomous, in particular with power supply from batteries. The new scientific concept is aimed at creating a resonance-type ETS for safe and reliable monitoring and diagnostics of the technical condition of high-voltage insulation of power cables, powerful electric machines and other energy objects of the critical infrastructure of Ukraine. Such ETS can also be effectively used for charging to high voltages capacitive energy storage (CES) in technological installations for the production of electro-spark micro- and nano-powders with unique properties, as well as for high-voltage electro-hydro-pulse processing of various materials and environments. It has been established that the power of these ETS increases with a decrease in the ratio of the capacitances of the capacitors ICC and CES. References 40, figures 4.